2017
DOI: 10.18632/oncotarget.16347
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the role of a fish-oriented diet in cognitive decline: a systematic review of the literature

Abstract: Epidemiological studies have presented inconsistent evidence of the correlation between a fish-oriented dietary intake (FDI) and the risk of cognitive decline. To address these controversies, we performed this systematic review of prospective studies published in December 2016 and earlier using PubMed, Embase, and Web of Science. Two independent researchers conducted the eligibility assessment and data extraction; all discrepancies were solved by discussion with a third researcher. The pooled relative risks (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
(93 reference statements)
0
17
2
1
Order By: Relevance
“…The findings in our study suggest that people with a good whole brain health condition, measured by FA-BHQ, tend to have lower risks of MCI. Although some previous studies found a direct effect of fish intake on prevention of MCI, the findings were limited and inconsistent (Zeng et al, 2017). Notably, the present study indicates that broader approaches can be used to prevent MCI by focusing on not only dietary factors but also FA-BHQ scores.…”
Section: Fa-bhq Mpicontrasting
confidence: 70%
See 1 more Smart Citation
“…The findings in our study suggest that people with a good whole brain health condition, measured by FA-BHQ, tend to have lower risks of MCI. Although some previous studies found a direct effect of fish intake on prevention of MCI, the findings were limited and inconsistent (Zeng et al, 2017). Notably, the present study indicates that broader approaches can be used to prevent MCI by focusing on not only dietary factors but also FA-BHQ scores.…”
Section: Fa-bhq Mpicontrasting
confidence: 70%
“…However, some studies have shown that fish consumption does not have a protective effect on MCI. A meta-analysis by Zeng et al (2017) found no statistically significant association between fish intake and the risk of MCI. The inconsistency in the association between fish intake and MCI may be due to indirectness.…”
Section: Introductionmentioning
confidence: 98%
“…The current study adds strength to this potentially important association. Other meta‐analyses have observed that higher fish intake is associated with decreased risk of dementia 58,60 and/or AD 58–61 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding fish intake, again, multiple systematic reviews have been conducted 17,58–62 . In a recent meta‐analysis of five cohort studies, higher fish intake was associated with slower decline in global cognition, particularly episodic memory 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Регулярное потребление обоих этих жиров может уменьшать эндотелиаль-ную дисфункцию, уровень триглицеридов и оказывать противовоспалительное действие. Систематический обзор проспективных исследований, включавших 28 754 субъекта, при сравнении максимального и наименьшего уровня потребления рыбы выявил суммарный относительный риск для БА, равный 0,80 (95% ДИ = 0,65-0,97), т. е. люди с более высоким потреблением рыбы имели 20%-ное (95% ДИ = 3-35%) снижение риска БА [35].…”
Section: питаниеunclassified